Metal-organic frameworks: functional luminescent and photonic materials for sensing applications - Lustig, William P; Mukherjee, Soumya; Rudd, Nathan D; Desai, Aamod V; Li, Jing; Ghosh, Sujit K (Chemical Society reviews, 2017)
Metal-organic frameworks (MOFs) or porous coordination polymers (PCPs) are open, crystalline supramolecular coordination architectures with porous facets. These chemically tailorable framework materials are the subject of intense and expansive research, and are particularly relevant in the fields of sensory materials and device engineering. As the subfield of MOF-based sensing has developed, many diverse chemical functionalities have been carefully and rationally implanted into the coordination nanospace of MOF materials. MOFs with widely varied fluorometric sensing properties have been developed using the design principles of crystal engineering and structure-property correlations, resulting in a large and rapidly growing body of literature. This work has led to advancements in a number of crucial sensing domains, including biomolecules, environmental toxins, explosives, ionic species, and many others. Furthermore, new classes of MOF sensory materials utilizing advanced signal transduction by devices based on MOF photonic crystals and thin films have been developed. This comprehensive review summarizes the topical developments in the field of luminescent MOF and MOF-based photonic crystals/thin film sensory materials. This review summarizes the diverse routes to derive sensing applications from suitably functionalized and crystal-engineered metal-organic framework (MOF) materials, either by fluorometric responses, or based on photonic crystal-based signal transduction.